Implementasi Terapi Relaksasi Benson untuk Menurunkan Intensitas Nyeri pada Pasien Stemi di Rumah Sakit Tentara TK IV 01.07.01 Pematangsiantar - Fahdilah, Soraya; Siregar, Nabilah (Green Publisher Indonesia, 2024)
STEMI is a heart disease that completely blocks the coronary arteries so that oxygen does not enter the heart muscle. The aim of this research is to determine the description of nursing care in the implementation of Benson relaxation therapy to reduce pain intensity in STEMI patients. This research design uses a case study method. The sampling method used is purposive sampling. The samples taken were 2 respondents from STEMI patients. The instruments used were emergency assessment format, Benson relaxation therapy SOP, evaluation sheet, pain observation sheet. The results obtained from this research were found to reduce pain intensity in client I, namely from a pain scale of 7 to 6 and in client II from a pain scale of 6 to 1. Benson relaxation therapy is effective for STEMI sufferers to reduce pain intensity.